Control of Mitotic Spindle Position by the Saccharomyces cerevisiae Formin Bni1p - Lee, Laifong (The Rockefeller University Press, 1999)
Alignment of the mitotic spindle with the axis of cell division is an essential process in Saccharomyces cerevisiae that is mediated by interactions between cytoplasmic microtubules and the cell cortex. We found that a cortical protein, the yeast formin Bni1p, was required for spindle orientation. Two striking abnormalities were observed in bni1Δ cells. First, the initial movement of the spindle pole body (SPB) toward the emerging bud was defective. This phenotype is similar to that previously observed in cells lacking the kinesin Kip3p and, in fact, BNI1 and KIP3 were found to be in the same genetic pathway. Second, abnormal pulling interactions between microtubules and the cortex appeared to cause preanaphase spindles in bni1Δ cells to transit back and forth between the mother and the bud. We therefore propose that Bni1p may localize or alter the function of cortical microtubule-binding sites in the bud. Additionally, we present evidence that other bipolar bud site determinants together with cortical actin are also required for spindle orientation.